2016
DOI: 10.1002/eap.1370
|View full text |Cite
|
Sign up to set email alerts
|

Linking landscape‐scale differences in forage to ungulate nutritional ecology

Abstract: Understanding how habitat and nutritional condition affect ungulate populations is necessary for informing management, particularly in areas experiencing carnivore recovery and declining ungulate population trends. Variations in forage species availability, plant phenological stage, and the abundance of forage make it challenging to understand landscape-level effects of nutrition on ungulates. We developed an integrated spatial modeling approach to estimate landscape-level elk (Cervus elaphus) nutritional reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 76 publications
4
81
0
Order By: Relevance
“…This dataset demonstrates that these decisions are crucial. Lower nutritive value diets can lead to higher mortality rates, lower pregnancy rates, production of fewer offspring and a higher risk of predation (Proffitt et al 2016). An analysis of 77 mammalian herbivores showed that larger animals better tolerate diets of lower nutritive quality because they can consume a greater volume of vegetation without increasing the efficiency of digestion (Müller et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This dataset demonstrates that these decisions are crucial. Lower nutritive value diets can lead to higher mortality rates, lower pregnancy rates, production of fewer offspring and a higher risk of predation (Proffitt et al 2016). An analysis of 77 mammalian herbivores showed that larger animals better tolerate diets of lower nutritive quality because they can consume a greater volume of vegetation without increasing the efficiency of digestion (Müller et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The size of the effect depends on the difference in the quality and availability of forage between origin and destination ranges, and the ability of individuals to replenish stores thereafter. This is much more difficult for ungulates in temperate regions in fall and winter than in spring and summer and thus the early-fall migration strategy could negatively impact pregnancy rates and calf survival in PAgroup elk (Cook et al 2004, Tollefson et al 2010, Hurley et al 2014, Proffitt et al 2016). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…, Proffitt et al. ), few studies have considered fall migration and the tradeoffs of forage and risk during that time period, likely because of the difficulties posed by the protracted and asynchronous nature of autumnal events (Gallinat et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional ecology, the study of the relationship between animals and their environment through nutritional interactions, has important implications for wildlife management and conservation (Parker et al 2009). Nutrition influences many aspects of animal life history, including pregnancy, reproductive success, juvenile growth and survival, and adult survival (Keech et al 2000, Cook et al 2004, Monteith et al 2014, Duquette et al 2015, Proffitt et al 2016). Understanding patterns of nutritional availability can improve inferences about effects of various limiting factors on population dynamics including disease, predation, climate, seasonal change, and habitat loss (Haskell and Ballard 2004, Long et al 2014, Monteith et al 2014, Downs et al 2015, Eacker et al 2016).…”
mentioning
confidence: 99%